Tactical performance of an Australian A-League association football team: comparing spatiotemporal data between different phases of play in matches - Hands, D. E.; O`Brien-Smith, J.; Janse de Jonge, X. A. K.; Livingston, G. C.; Borges, N. R. (International Journal of Performance Analysis in Sport, 2026)
This study investigated the effect of phases of play during association football matches on spatiotemporal measures of tactical performance, for an Australian A-League team. Phases of play were identified from video recordings of 10 official A-League matches and synchronised to 10 Hz GPS data. The GPS data were used to calculate measures of a team`s average position relative to the playing field (team centroid distance from the goal-line), dispersion (stretch index), playing space (effective area); and a measure of individual player space (spatial exploration index). Three analysis of variance models compared between phases of play for the team measures, and a mixed model compared between phases of play for the individual player measure. Stretch index and effective area were greatest in "build-up play", then "counter-attack", then "counter-defending" (each p < 0.005). There was no significant difference between the "defensive block" and "other" phases; or between any phases of play for team centroid distance from the goal-line. Spatial exploration index was greatest (p < 0.001) in the "other" phase of play and lowest (p < 0.02) in "defensive block". The phases of play framework highlights differences between the types of possession that would otherwise not be shown, providing useful performance context.